CORRUPTION AND NICCOLO MACHIAVELLI - Tomy Michael (Association of Certified Fraud Examiners Indonesia Chapter, 2016)
The increasing corruption in Indonesia occurs because of the indecision of the leader. This is contrary to the 1945 Constitution of the republic of Indonesia that the position of the president is the chief executive. This has repercussions on the position where the president to act without pressure in combating corruption. The leader can apply the Niccolo Machiavelli’s idea that is to take the ideas of the people and focus on those ideas, and then restore those ideas to the people so that they apply them, and to make corrections in case of errors. Such is the basic method of leadership. In conclusion, Niccolo Machiavelli’s ideais appropriate to be applied in combating corruption because in the Law Bo. 20 of 2001 has created a justice for the perpetrators of corruption when declared as the accused of corruption. The main concern is to take advantage with the position of president as the chief executive, in which the president may also be subject to the decisive law. This firm attitude will have an impact on law enforcement to implement legislation fairly. The suggestions that can be put forward in combating corruption is understanding the doctrine of jurisprudence, from countries, that are considered poor should be a critical review in the development of legal science in Indonesia, extending the meaning of gratification by incorporating sexual elements, and applying social sanctions.